The Effect Of Peer Education On Knowledge About The Dangers Of Early Marriage In Mimika Regency, Papua Province - Kainde, Yuliana Yacinta; Siregar, Neny San Agustina; Arisjulyanto, Dedy (Jurnal EduHealth, 2024)
This study aims to evaluate the effectiveness of the Community Empowerment program through the peer education method in preventing child marriage among adolescents in Mimika Regency. The research employs a quantitative approach with a quasi-experimental study design. The population consists of adolescents aged 15-18 years in Mimika Regency. A purposive sampling technique was used to select 65 respondents who participated in the community empowerment program through peer education for three months. The program's impact was assessed by measuring changes in adolescents' knowledge, attitudes, and intentions to delay marriage. The study found that the mean knowledge score about child marriage increased from 31.20 before the intervention to 39.28 after the intervention. The statistical analysis showed a significant effect (p-value = 0.000, α < 0.05). The study is limited to a small sample size within Mimika Regency, which may affect the generalizability of the findings. Furthermore, the quasi-experimental design lacks a control group, which could influence the robustness of the conclusions. This research contributes to public health and adolescent development studies by highlighting the potential of peer education as an effective method to improve knowledge regarding the prevention of child marriage. The findings provide a framework for policymakers and community organizations aiming to reduce child marriage rates in similar regions.